ANTI-BACTERIAL PROPERTY OF A CORAL-ASSOCIATED BACTERIUM Bacillus sp. AGAINST CORAL PATHOGENIC BBD (BLACK BAND DISEASE) - Agus Sabdono; Ocky Karna Radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Marine organisms such as corals are frequently colonized by bacteria that may be pathogenicto them. One of the means by which they are able to combat microbial attack is by chemical defense. Anumber of metabolites obtained from algae and invertebrates may be produced by associatedmicroorganisms. The purpose of study was to isolate and characterize of coral-associated bacteriahaving antibacterial potency against BBD coral disease. A coral-associated bacterium, KM2 isolate,was successfully screened for antibacteria production against indigenous BBD pathogenic bacteriabased on PCR amplification of the non-ribosomal peptide synthetase gene and was identified as closelyrelated to Bacilus sp based on its 16S rDNA.. KM2 strain was found to inhibit the growth of coralpathogenic BBD bacteria tested Myroides odoratimimus strain BBD1, Bacillus algicola Strain BBD2and Marine Alcaligenes bacterium Strain BBD3. This bacterium was found to inhibit the growth of allthose BBD coral pathogenic bacteria.